Efficient shielding gas supply for laser-based Powder Bed Fusion of metals (PBF-LB/M) - Medvedev, Vadim; Kopp, Sebastian-Paul; Nahr, Florian; Roth, Stephan (Procedia CIRP, 2024)
The inert gas supply during laser-based powder bed fusion of metals (PBF-LB/M) is one of the most important sub-processes influencing the quality of the end products and the efficiency of the printing process. However, improper distribution of the shielding gas flow can result in poor part quality and excessive energy and gas consumption. Thus, the formation of a homogeneous protective gas flow over the powder melting region is crucial to minimize the negative effects mentioned above. In this investigation, a modified system for supplying shielding gas to the building chamber of PBF-LB/M machine is developed with the possibility of creating localized and uniform gas flows over the area where the melting process takes place. The aim of the selectively localizable shielding gas supply is to improve process efficiency of PBF-LB/M while giving the opportunity to enhance part properties such as surface roughness.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Additive Manufacturing; AlSi10Mg; process efficiency; Selective laser melting; shielding gas flow